Dehumidifying film as well as preparation method and application thereof

By using modified polyester, modified polyvinylidene fluoride and polymer in the dehumidification film, the pore structure of the film layer is optimized, and the problems of low porosity, poor pore connectivity and poor strength of the existing dehumidification film are solved. Achieve more efficient dehumidification and longer service life.

CN119425413APending Publication Date: 2025-02-14GUANG DONG MO DUO WEI LAI KE JI YOU XIAN GONG SI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411830632.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing dehumidification films have problems such as low porosity, poor pore connectivity and poor strength, which are difficult to meet the current demand for dehumidification film materials.

Method used

A dehumidification film consisting of modified polyester, modified polyvinylidene fluoride, and a film layer, which includes 10-30 parts of inorganic salt, 5-20 parts of filler, and 50-80 parts of polymer, through optimization The pore structure and performance of the membrane layer improves the dehumidification efficiency.

Benefits of technology

It significantly improves the porosity and pore connectivity of the dehumidification film, enhances the mechanical strength of the film, improves the dehumidification efficiency, and extends the service life of the dehumidifier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of dehumidification, and particularly relates to a dehumidification film as well as a preparation method and application thereof. The dehumidification film comprises a film layer, a protective layer and a supporting layer located between the film layer and the protective layer, the protective layer is made of modified polyester, the supporting layer is made of modified polyvinylidene fluoride, and the film layer comprises, by mass, 10-30 parts of inorganic salt, 5-20 parts of filler and 50-80 parts of high polymer. According to the dehumidification film, by optimizing the composition and structure of the film layer, the supporting layer and the protective layer, the porosity and pore connectivity are remarkably improved, the mechanical strength of the film is enhanced, and the dehumidification efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dehumidification, and in particular relates to a dehumidification membrane, and a preparation method and application thereof. Background Art

[0002] Humidity plays a vital role in the indoor environment. It directly affects people's comfort and health, and also affects the service life of items inside the building. Whether it is too dry or too humid, it is not conducive to the preservation of furniture and other items. For special places such as museums and libraries, precise control of indoor humidity is even more important to prevent damage to exhibits or books.

[0003] In the actual application of indoor temperature and humidity control, condensation dehumidification is a common method. Its core principle is to reduce the outdoor air temperature to below the water vapor dew point, so that the water vapor condenses into water droplets on the fan coil, and then raise the temperature to the set value. However, this dehumidification method has the problem of large energy loss, and the condensed water on the fan coil is easy to breed mold, which has a negative impact on the indoor air quality.

[0004] Compared with condensation dehumidification, membrane dehumidification, as an emerging dehumidification technology, has shown great research and development potential and many advantages. It avoids the corrosion problem in traditional dehumidification methods, does not require complex valve switching operations, and has no moving parts, so it has higher reliability and easy maintenance. In addition, membrane dehumidification also has the advantage of low energy consumption. In the membrane dehumidification process, the dehumidification membrane is installed on the dehumidifier as a key component. The concentration difference between water vapor and other components in the air is used, and the water vapor is driven by pressure or temperature to selectively pass through the dehumidification membrane, thereby achieving gas dehumidification and filtration.

[0005] Common dehumidification membranes such as polyethersulfone, polyvinylidene fluoride, mixed cellulose esters, and polymer membranes composed of polydisiloxane and polyvinyl alcohol currently have problems such as low porosity, poor pore connectivity, and poor strength, which makes it difficult to meet people's current urgent demand for dehumidification membrane materials.

[0006] Therefore, it is necessary to develop a dehumidification membrane and a preparation method thereof, which can be better applied in dehumidifiers, thereby improving the efficiency of the dehumidification process and better improving the user experience. Summary of the invention

[0007] The purpose of the present invention is to overcome the technical problems of low porosity, poor pore connectivity and poor strength commonly found in the above-mentioned dehumidification membranes, thereby providing a dehumidification membrane, and a preparation method and application thereof.

[0008] For a dehumidification membrane, the present invention adopts the following technical solution: A dehumidification membrane comprises a membrane layer, a protective layer, and a support layer located between the membrane layer and the protective layer, wherein the protective layer is modified polyester, and the support layer is modified polyvinylidene fluoride. Calculated by mass, the membrane layer comprises 10-30 parts of inorganic salt, 5-20 parts of filler, and 50-80 parts of polymer.

[0009] Specifically, the protective layer is made of modified polyester material, which has good flexibility, wear resistance, weather resistance, and chemical corrosion resistance, and can protect the film layer from scratches and wear. Compared with ordinary polyester, modified polyester can allow water to pass better, thereby improving the dehumidification effect.

[0010] Specifically, the support layer is made of modified polyvinylidene fluoride, which has high mechanical strength and good chemical stability, can effectively support the membrane layer, prevent it from deformation or rupture during use, and improve the durability of the entire dehumidification membrane. In addition, it has good flexibility and certain porous structural characteristics, which can provide support for the membrane layer to a certain extent, prevent the pores of the membrane layer from being squeezed and closed due to factors such as pressure during preparation or use, and help maintain the porosity of the membrane layer.

[0011] Specifically, the membrane layer has an optimized pore structure and good pore connectivity, which allows water vapor to pass through the membrane layer more quickly, thereby improving the dehumidification efficiency. Inorganic salt particles can promote the polymer to form a more complex structure during the molding process in the polymer matrix, increasing the number of pores inside the membrane layer. Fillers can also open up the molecular chains of polymers to prevent them from being too densely packed, thereby increasing the porosity. The addition of inorganic salts and fillers helps to improve the membrane layer's ability to adsorb moisture and further enhance the dehumidification effect, while polymers provide a certain degree of flexibility and strength.

[0012] Furthermore, the inorganic salt includes one of calcium chloride and lithium chloride, the filler includes one or more of carboxyl mesoporous silica, silver-zinc-loaded zeolite, and modified attapulgite, and the polymer includes one or more of lauroyl sulfate deacetylated chitosan, polyether block polyamide, and polyvinyl alcohol.

[0013] Specifically, by optimizing the pore structure and performance of the membrane layer, the membrane layer structure allows water vapor to pass through the membrane layer more quickly, thereby improving the dehumidification efficiency. The synergistic effect of inorganic salts and fillers forms a uniform and dense microporous structure inside the membrane layer, improving the porosity and pore connectivity; while the addition of polymers enhances the mechanical strength and chemical stability of the membrane layer.

[0014] Specifically, calcium chloride and lithium chloride are both effective desiccant. Calcium chloride can form hydrates with water, and lithium chloride can also absorb a large amount of water molecules. By increasing the ability of the membrane layer to capture water vapor, the moisture absorption capacity of the membrane layer can be significantly improved, thereby enhancing the dehumidification effect. Calcium chloride or lithium chloride forms a microporous structure inside the membrane layer, which helps to improve the porosity and pore connectivity. Based on its good water solubility and thermal stability, it ensures that it can be evenly dispersed in the membrane layer during the preparation process and effectively removed in subsequent treatments without leaving any residue.

[0015] Specifically, the filler not only has excellent adsorption properties, can enhance the adsorption capacity of the membrane layer for water, but also improves the connectivity of the pores, so that water vapor can pass through the membrane layer more smoothly. Carboxyl mesoporous silica has a large specific surface area and mesoporous structure. Its mesopores can provide a large number of adsorption sites, which helps to improve the pore structure of the membrane layer, increase the connectivity and regularity of the pores, so that water vapor can be transmitted more smoothly in the membrane layer, and the presence of carboxyl groups can enhance the adsorption of water molecules. Silver-zinc zeolite also has antibacterial properties, can inhibit the growth of mold on the membrane layer, and improve the hygienic properties of the dehumidification membrane. Zeolite can enhance the structural stability in the membrane layer, which helps to improve the strength of the entire dehumidification membrane. Modified attapulgite has good adsorption and ion exchange capacity, can form channels in the membrane layer that are conducive to water vapor transmission, improve the connectivity of the pores inside the membrane layer, and improve the dehumidification performance of the dehumidification membrane.

[0016] Specifically, polymers have good film-forming properties and chemical stability, and can form a tough and dense film structure. At the same time, they also have certain hydrophilicity and air permeability, which helps to balance the water permeability and mechanical strength of the film layer and improve the dehumidification efficiency. Lauroyl sulfate deacetylated chitosan has a certain adsorption effect on water vapor. Lauroyl sulfate deacetylated chitosan has antibacterial properties. At the same time, by introducing hydrophobic groups and sulfate groups, the mechanical strength and chemical resistance of the film layer are improved, and the functional groups on the molecular chain can interact with fillers or inorganic salts to enhance the integrity of the film layer. Lauroyl sulfate deacetylated chitosan helps to improve the film-forming properties of the film layer, so that the film layer can be evenly formed on the supporting layer, ensuring the overall stability of the dehumidification membrane. Polyether block polyamide has good flexibility, can maintain good physical properties, and is not easy to break. Polyether block polyamide has a certain selective permeability to water vapor, which allows water vapor to pass preferentially, and has a certain barrier effect on other gases, thereby improving the dehumidification efficiency of the dehumidification membrane. Polyvinyl alcohol has good hydrophilicity, which helps to improve the film's ability to adsorb water vapor. It also has good film-forming properties, which can make the film form a uniform and continuous film to ensure the overall performance of the dehumidification film. At the same time, the interaction between its molecular chains also helps to improve the strength of the film.

[0017] Furthermore, the preparation method of the modified attapulgite comprises the following steps: M1. Grind and crush the attapulgite, sieve it to 80-200 mesh, add hydrochloric acid and stir it, wash it with deionized water, centrifuge and dehydrate it, and dry it; First, grind and crush the attapulgite to ensure that its particle size is uniform. Then, the particle size is controlled between 80-200 mesh by screening. Add hydrochloric acid to the sieved attapulgite and stir it. Hydrochloric acid can react with impurities and some mineral components in the attapulgite, thereby improving its surface properties and pore structure. After the stirring treatment is completed, wash it with deionized water until the eluate is neutral to remove excess hydrochloric acid and impurities, then remove water by centrifugal dehydration, and finally dry it at 60-100°C for 2-4 hours to obtain acidified attapulgite. Specifically, the hydrochloric acid concentration is 6 mol / L, and the mixture is mixed according to the solid-liquid ratio of 1:10, and the stirring time is about 1-4 hours.

[0018] M2, the acidified attapulgite is added to ethanol, and it is fully dispersed by ultrasonic treatment to obtain an attapulgite ethanol suspension; the acidified attapulgite is added to anhydrous ethanol, and it is fully dispersed by ultrasonic treatment for 30 minutes to 1 hour, and the obtained suspension concentration is 5wt%. Ethanol can reduce the interaction force between attapulgite particles, making it easier to disperse and form a suspension. Ultrasonic treatment can further enhance the dispersion effect and ensure that the attapulgite particles are evenly distributed in ethanol.

[0019] M3. Add the ethanol suspension of attapulgite to the silane coupling agent γ-methacryloxypropyltrimethoxysilane-ethanol working solution with a mass fraction of 1-5%, heat to 60-80°C, continue stirring for 2-4 hours, centrifuge after the reaction is completed, wash with ethanol, and dry to obtain modified attapulgite for later use. Add the ethanol suspension of attapulgite to the silane coupling agent working solution. The silane coupling agent can react with the hydroxyl functional groups on the surface of the attapulgite to form chemical bonds, thereby improving its surface properties and interface compatibility.

[0020] Specifically, under the condition of temperature increase, the silane coupling agent and the attapulgite are stirred evenly to fully react. After the reaction is completed, the modified attapulgite is separated from the suspension by centrifugal separation, washed with ethanol to remove unreacted silane coupling agent and impurities, and finally dried to obtain modified attapulgite for standby use.

[0021] Specifically, through acidification and modification, the surface properties and pore structure of attapulgite have been significantly improved, improving its performance in water vapor adsorption and permeation. The interface compatibility of the modified attapulgite with polymer and other membrane materials has been enhanced, which helps to improve the overall performance and stability of the membrane, making the membrane more durable and less prone to damage in actual use.

[0022] Furthermore, the preparation method of lauroyl sulfate deacetylated chitosan comprises the following steps: N1. Mix the pretreated chitosan with sodium hydroxide solution and react at high temperature to obtain deacetylated chitosan. First, pretreat the chitosan by crushing, screening, etc. to ensure that its particle size is uniform for subsequent reaction. Mix 5g of pretreated chitosan with 40wt% sodium hydroxide solution and react at high temperature of 80-100℃ for 2-4 hours. The role of sodium hydroxide is to react with the acetyl group in chitosan to generate deacetylated chitosan.

[0023] N2. Weigh 5 grams of deacetylated chitosan to prepare a 10wt% deacetylated chitosan-ethanol solution. Slowly add 1.5 ml of lauroyl chloride under stirring, and react at room temperature to 60°C for 0.5-2 hours. After the reaction, wash with a solvent and vacuum dry overnight at 60-80°C to obtain lauroyl chitosan; dissolve the deacetylated chitosan in ethanol to obtain a uniform solution. Ethanol as a solvent can reduce the viscosity of the solution and improve the reaction efficiency.

[0024] Specifically, lauroyl chloride is slowly added dropwise to the deacetylated chitosan-ethanol solution under stirring. Lauroyl chloride can react with the hydroxyl group in the deacetylated chitosan to generate lauroyl chitosan. The reaction needs to be carried out at room temperature to 60°C, and the reaction time is 0.5-2 hours. After the reaction is completed, the product is washed with a solvent (such as ethanol, water, etc.) to remove unreacted lauroyl chloride and impurities, and then dried.

[0025] N3. Weigh 5 grams of lauroyl chitosan to prepare a 10wt% lauroyl chitosan-ethanol solution. After adjusting the pH to 9-10, slowly add 2 ml of dimethyl sulfate under stirring, and react at room temperature for 2-4 hours. After the reaction is completed, pour the reaction solution into a large amount of deionized water to precipitate the product. After washing and drying, lauroyl sulfate deacetylated chitosan is obtained for standby use. Dissolve lauroyl chitosan in ethanol to obtain a uniform solution. Adjust the pH of the solution to 9-10, and then slowly add dimethyl sulfate under stirring. Dimethyl sulfate can react with the hydroxyl group in lauroyl chitosan to generate lauroyl sulfate deacetylated chitosan. The reaction needs to be carried out at room temperature, and the reaction time is generally 2-4 hours. After the reaction is completed, pour the reaction solution into a large amount of deionized water to precipitate the product. Pure lauroyl sulfate deacetylated chitosan is obtained by centrifugation, washing, and vacuum drying overnight at 60-80°C.

[0026] Specifically, through chemical reactions such as deacetylation, acylation and sulfation, the structure of lauroyl sulfate deacetylated chitosan has been optimized, with specific functional groups and segment structures, thereby improving its performance in water vapor adsorption, permeation and membrane compatibility. The modified chitosan can better combine with inorganic salts and fillers to form a more uniform and stable membrane structure, improving the overall performance. The modified chitosan has better compatibility with the modified polyvinylidene fluoride support layer in the dehumidification membrane, enhancing the overall stability of the dehumidification membrane.

[0027] Specifically, the modified chitosan added as a polymer component to the membrane layer can significantly improve the porosity and pore connectivity of the dehumidification membrane, and enhance its adsorption and permeation capacity for water vapor. At the same time, due to the introduction of specific functional groups, such as sulfate ions and lauroyl groups, it may also give the dehumidification membrane certain antibacterial properties and thermal stability.

[0028] Furthermore, the preparation method of the silver-zinc-loaded zeolite comprises the following steps: P1. Grind the zeolite through a 60-80 mesh sieve and activate it with a hydrochloric acid solution at room temperature to obtain the pretreated zeolite; grind the original zeolite and sieve it through a 60-80 mesh sieve to ensure that its particle size is uniform and convenient for subsequent processing. The sieved zeolite is activated with a 1-3 mol / L hydrochloric acid solution at room temperature, and stirred for 1-2 hours according to a solid-liquid ratio of 1:10. The role of hydrochloric acid is to react with impurities and some mineral components on the surface of the zeolite, thereby improving its surface properties and pore structure, and improving its adsorption capacity for metal ions. After the activation treatment is completed, wash the zeolite with deionized water until the eluate is neutral to remove excess hydrochloric acid and impurities, and dry it at 60-100°C for 2-4 hours to obtain the pretreated zeolite.

[0029] P2. Dissolve zinc nitrate in deionized water, add the pretreated zeolite to a 0.1-0.5M zinc nitrate mixed solution, and stir at 60-80°C for 2-4 hours to obtain zinc-modified zeolite; dissolve zinc nitrate in deionized water to obtain a uniform zinc solution. Add the pretreated zeolite to the zinc solution and stir at 60-80°C for 2-4 hours. In this process, zinc ions will be adsorbed into the pores and surface of the zeolite to form zinc-modified zeolite. After stirring, wash the zinc-modified zeolite with deionized water to remove unadsorbed zinc ions and impurities.

[0030] P3. Immerse the zinc-modified zeolite in a solution containing silver ions and glucose, and react at 60-80°C for 1-2 hours; mix a 0.1-0.5mM silver nitrate solution with 1-5wt% glucose to obtain a mixed solution containing silver ions and glucose. Glucose, as a reducing agent, can reduce silver ions to silver nanoparticles in subsequent reactions. Immerse the zinc-modified zeolite in the above mixed solution and react at 60-80°C for 1-2 hours. In this process, silver ions will be adsorbed on the surface of the zinc-modified zeolite and reduced to silver nanoparticles under the action of glucose, thereby obtaining silver-loaded zinc zeolite.

[0031] P4. After the reaction is completed, wash and dry the silver-zinc zeolite for standby use. After the reaction is completed, wash the silver-zinc zeolite with deionized water to remove unabsorbed silver ions, glucose and other impurities. Then, vacuum dry the washed silver-zinc zeolite at 60-80° C. overnight to obtain pure silver-zinc zeolite for standby use.

[0032] Specifically, by loading silver nanoparticles, silver-zinc-loaded zeolite has significant antibacterial properties, can inhibit the growth of mold on the membrane layer, and improve the hygienic properties and service life of the dehumidification membrane. The introduction of zinc ions not only improves the surface properties and pore structure of zeolite, but also improves its adsorption capacity for water vapor. At the same time, the loading of silver nanoparticles also increases the surface area and active sites of zeolite, further enhancing its adsorption performance. The structure of silver-zinc-loaded zeolite is stable, not easily affected by the external environment, and can maintain its excellent performance for a long time.

[0033] The support layer is made of polyvinylidene fluoride and cellulose acetate. Furthermore, the preparation method of the modified polyvinylidene fluoride comprises the following steps: Q1. Dissolve polyvinylidene fluoride and cellulose acetate in a mixed solvent of 50-70wt% N,N-dimethylacetamide and 30-50wt% acetone to obtain a first composite spinning solution; select a mixed solvent of N,N-dimethylacetamide and acetone to dissolve polyvinylidene fluoride and cellulose acetate and dissolve polyvinylidene fluoride alone. The mixture of these two solvents may have a synergistic effect, which can better dissolve polyvinylidene fluoride and cellulose acetate, so that the solute molecules can be evenly dispersed in the solvent. For polyvinylidene fluoride, the mixed solvent can destroy the intermolecular forces, so that its molecular chains can be fully stretched, which is conducive to the formation of a regular fiber structure in the subsequent spinning process. Take polyvinylidene fluoride and cellulose acetate raw materials in a weight ratio of 1:1, and prepare a mixed solvent in a mass ratio of 1:1. The mass concentration of the composite spinning solution of polyvinylidene fluoride and cellulose acetate is about 24%, and the absolute viscosity is 5.5pa.s. The introduction of cellulose acetate improves the hydrophilicity of the material and also gives the material certain antibacterial properties, preventing the growth of microorganisms and keeping the membrane clean and hygienic.

[0034] Q2. Dissolve polyvinylidene fluoride in a mixed solvent of N,N-dimethylacetamide and acetone to obtain a polyvinylidene fluoride spinning solution; the proportion of the mixed solvent can adjust the viscosity, surface tension and other properties of the spinning solution. Appropriate viscosity can ensure that the solution can be stably extruded from the nozzle during the spinning process and form continuous fibers under the action of the electric field, while appropriate surface tension helps control the diameter and shape of the fiber. The mass concentration of the polyvinylidene fluoride spinning solution is about 10%, and the absolute viscosity is 1.2pa.s.

[0035] Q3. Use two sets of electrospinning heads to extrude the first composite spinning solution and the polyvinylidene fluoride spinning solution respectively to form a three-layer composite nonwoven fabric with different fiber diameters; Use two sets of electrospinning heads to extrude the first composite spinning solution and the polyvinylidene fluoride spinning solution respectively to form a three-layer composite nonwoven fabric with different fiber diameters. This composite structure can combine the advantages of different fiber diameters. Finer fibers can provide a larger specific surface area, which is conducive to interaction with the external environment. For example, in a dehumidification membrane, it can increase the adsorption and diffusion area of ​​water vapor; while thicker fibers can provide better mechanical support and enhance the strength of the entire nonwoven fabric.

[0036] Specifically, the first layer and the third layer use the first composite spinning solution, and the middle layer uses the polyvinylidene fluoride spinning solution to form a "sandwich" structure. The three-layer composite structure can also form a layered functional system. The middle layer can play a special functional role such as enhancing adsorption capacity, while the inner and outer layers can play a protective and supporting role, improving the stability and durability of the entire structure. The combination of different fiber diameters can achieve synergistic optimization of multiple properties. In terms of dehumidification, the layer with a smaller fiber diameter may have better water vapor permeability, while the layer with a larger fiber diameter can prevent structural collapse and ensure the continuation of the dehumidification process. At the same time, this composite structure also shows synergy in mechanical properties, such as improving tensile and compressive properties, so that the structure can remain intact in the operating environment of the dehumidifier.

[0037] Q4. Introduce the nonwoven fabric into a drying furnace at 100-150°C to remove the residual solvent in the fiber. Introduce the nonwoven fabric into a drying furnace at 100-150°C to remove the residual solvent in the fiber. The presence of residual solvent may affect the structural stability of the fiber. After removing the solvent, the molecular structure inside the fiber can be arranged more closely, improving the strength of the fiber itself, thereby enhancing the structural stability of the entire three-layer composite structure nonwoven fabric. In the application of the three-layer composite structure of polyvinylidene fluoride in the dehumidification membrane, it not only improves the mechanical strength, porosity and air permeability of the support layer, but also enhances the overall performance and durability of the membrane. This enables the dehumidification membrane to work stably for a long time in various complex environments.

[0038] Furthermore, the method for preparing the film layer comprises the following steps: T1. Add the polymer to the solvent, stir it at 60-80℃ for 2-4 hours with a magnetic stirrer until the polymer is completely dissolved to prepare a polymer solution; add the polymer to an appropriate solvent N,N-dimethylacetamide, stir it at 60-80℃ for 2-4 hours with a magnetic stirrer. The synergistic effect of high temperature and stirring can break the forces between polymer molecules, ensuring that the polymer is completely dissolved in the solvent to form a uniform polymer solution, which helps to form a film layer with stable performance. If the polymer is not completely dissolved, there will be local uneven concentration in the film layer, affecting the overall performance of the film layer.

[0039] T2. Dissolve the inorganic salt in a mixed solvent of 50-70wt% N,N-dimethylacetamide and 30-50wt% acetone, prepare the mixed solvent in a mass ratio of 1:1, add the filler and continue to stir with a stirrer to obtain a mixed solution; dissolve the inorganic salt and add the filler, and continue to stir to obtain a uniform mixed solution. The stability of this mixed solution helps to mix with the polymer solution in the subsequent steps to form a stable spinning solution. Specifically, the stirring process can prevent the filler from agglomerating, so that the inorganic salt and the filler are evenly distributed in the solution. In the membrane layer, the evenly distributed inorganic salt and filler help to achieve uniform dehumidification effect, strength distribution and pore connectivity. If the filler agglomerates or the inorganic salt is unevenly distributed, it may cause excessive differences in the local performance of the membrane layer, such as good dehumidification effect in some areas and poor dehumidification effect in other areas, or low local strength.

[0040] T3. Gradually add the polymer solution to the mixed solution and stir until all components are completely dissolved to form a spinning solution. This step ensures the uniform distribution of the components in the spinning solution, which helps to form a uniform fiber and membrane layer during the electrospinning process. The concentration of the spinning solution is between 15% and 30%.

[0041] T4. The spinning solution is placed in a vacuum dryer for vacuum degassing for 1-3 hours. The spinning solution is placed in a vacuum dryer for vacuum degassing for 1-3 hours. This process effectively removes the bubbles in the spinning solution, improves the quality of the spinning solution, and thus reduces the breakage of the fiber and the unevenness of the film layer during the spinning process.

[0042] T5. Inject the spinning solution into the spinning equipment, spin the spinning solution into fibers by electrospinning, and form a membrane layer on the receiving device. The spinning solution is spun into fibers by electrospinning technology, and a membrane layer is formed on the receiving device. Electrospinning technology has the advantages of small fiber diameter, large specific surface area, high porosity, and good air permeability, so that the prepared membrane layer has excellent performance. The large specific surface area of ​​the membrane layer helps to improve the dehumidification efficiency of the membrane layer, because more of the membrane layer surface can be in contact with water vapor. At the same time, the fiber structure of the membrane layer formed by electrospinning can control the porosity and pore connectivity of the membrane layer, which is beneficial to the transmission of water vapor and can improve the strength of the membrane layer to a certain extent. The inorganic salts and fillers in the membrane layer can enhance the mechanical strength, chemical stability and thermal stability of the membrane layer, while improving its filtration performance, separation performance and adsorption performance.

[0043] The protective layer is made of polyester and polyvinyl alcohol. Furthermore, the preparation method of the protective layer comprises the following steps: V1. Dissolve polyester and polyvinyl alcohol in a solvent, and stir with a magnetic stirrer to obtain a polyester mixed solution; add polyester and polyvinyl alcohol to N,N-dimethylacetamide in a mass ratio of 80:20, and stir with a magnetic stirrer at 60-80°C for 2-4 hours to ensure that the polyester and polyvinyl alcohol are completely dissolved to obtain a uniform polyester mixed solution. The stirring action of the magnetic stirrer can fully mix the polyester and polyvinyl alcohol in the solvent. The mixture of these two polymers can combine the advantages of both, for example, polyester may provide better mechanical properties, and polyvinyl alcohol may provide better hydrophilicity or film-forming properties, etc., to improve the moisture permeability of the protective layer.

[0044] V2. Pour the polyester mixed solution on a flat plate, scrape it flat with a scraper to form a uniform film, and dry it at 60-80°C for 2-4 hours until the solvent is completely volatilized to obtain a modified polyester; Pour the polyester mixed solution on a flat plate and scrape it flat with a scraper to form a uniform film. The scraping operation can ensure that the thickness of the film is uniform. A film with uniform thickness can provide consistent protection performance in the entire protection area and avoid local weak points. Dry at 60-80°C for 2-4 hours until the solvent is completely volatilized to obtain a modified polyester. Appropriate drying temperature and time can ensure that the solvent is completely removed, making the structure of the film more stable. If the solvent remains, it may affect the mechanical properties and chemical stability of the film. The modified polyester after complete drying has a stable structure and can better play a protective role.

[0045] Furthermore, another object of the present invention is to provide a method for preparing a dehumidification membrane, comprising the following steps: S1. Prepare a protective layer and a support layer separately, and the protective layer and the support layer form a composite film layer through a compacting composite process; combine the protective layer and the support layer together through a compacting composite process to form a composite film layer. This composite structure combines the respective advantages of the protective layer and the support layer, such as the weather resistance, chemical corrosion resistance and waterproof and antifouling properties of the protective layer, and the mechanical strength and stability of the support layer. Therefore, the composite film layer has excellent comprehensive properties and provides a good foundation for the subsequent electrospinning process. Compressed composite can ensure that the two layers of materials are tightly combined without bubbles or gaps through a hot press. The thickness of the protective layer is 10-50μm. If the protective layer is too thick, it may cause a greater obstacle to the penetration of water vapor and affect the dehumidification efficiency; if it is too thin, it may not be able to effectively play a protective role. The support layer is a thicker layer in the dehumidification membrane, which mainly plays a supporting and protective role. The thickness of the support layer is 100-200μm.

[0046] S2. Prepare the membrane layer into a membrane spinning solution, and apply the membrane spinning solution to one side of the support layer of the composite membrane layer through an electrospinning process to obtain a dehumidification membrane. Prepare the membrane layer into a membrane spinning solution, and apply it to one side of the support layer of the composite membrane layer through an electrospinning process. The electrospinning process has the characteristics of efficient, continuous and controllable preparation of nano-scale fibers, and can form a dehumidification membrane with a micro-nano structure. This structure has a high specific surface area and porosity, which is conducive to the adsorption and transmission of moisture, thereby improving the dehumidification efficiency of the dehumidification membrane. The spinning solution flow rate of the spinning process is 5-10mL / h, a high-voltage DC power supply is used, the nozzle voltage is set at 30-40kV, the receiving distance is 15-22cm, the temperature is 25℃~28℃, the humidity is 35%~40%, and the membrane thickness is 10-100μm. This thickness range helps water vapor to diffuse quickly through the membrane layer to achieve efficient dehumidification.

[0047] Specifically, by adjusting the composition, concentration, spinning voltage, receiving distance and other parameters of the membrane spinning solution, the microstructure of the dehumidification membrane, such as fiber diameter, pore size and distribution, can be precisely controlled. This precise control helps to optimize the performance of the dehumidification membrane, such as improving the adsorption capacity of moisture, reducing the resistance to moisture transmission, and enhancing the mechanical strength of the dehumidification membrane. The presence of the protective layer provides an additional protective layer for the dehumidification membrane, which can prevent moisture from eroding and damaging the support layer, thereby extending the service life of the dehumidification membrane. At the same time, the weather resistance and chemical corrosion resistance of the protective layer also help to improve the stability and durability of the dehumidification membrane in harsh environments. The entire preparation process, from the preparation of the protective layer and the support layer, the formation of the composite membrane layer, the preparation of the membrane spinning solution to the implementation of the electrospinning process, has good controllability and flexibility.

[0048] Furthermore, another object of the present invention is to provide an application of a dehumidification membrane, and to use the prepared dehumidification membrane in a dehumidifier.

[0049] Specifically, the dehumidification membrane has a micro-nanoscale pore structure and a high specific surface area, and can efficiently adsorb and transmit moisture. Applying it to a dehumidifier can significantly improve the dehumidification efficiency of the dehumidifier, so that the dehumidifier can quickly reduce the indoor humidity in a short time and achieve an ideal dehumidification effect. The application of the dehumidification membrane can also effectively extend the service life of the dehumidifier. Since the dehumidification membrane can efficiently adsorb and remove moisture, it can reduce the corrosion and wear of the internal components of the dehumidifier, reduce the failure rate, and thus extend the service life of the dehumidifier. By adjusting the thickness, pore size, and distribution of the dehumidification membrane, the dehumidification speed and humidity adjustment range of the dehumidifier can be accurately controlled to meet different usage requirements. At the same time, the dehumidification membrane can also be used as a filter layer for the dehumidifier to effectively remove harmful substances such as dust and bacteria in the air and improve the indoor air quality.

[0050] Compared with the prior art, the present invention has the following advantages: 1. The dehumidification membrane of the present invention significantly improves the porosity and pore connectivity by optimizing the composition and structure of the membrane layer, the support layer and the protective layer, enhances the mechanical strength of the membrane, and can improve the dehumidification efficiency.

[0051] 2. The preparation method of the present invention can ensure the excellent performance of the composite membrane layer, the high efficiency of the electrospinning membrane layer, the performance optimization of the dehumidification membrane, the long-term stability, the controllability and flexibility of the preparation process and the wide application field, so that the prepared dehumidification membrane has broad application prospects and market demand.

[0052] 3. The dehumidification membrane of the present invention is applied to a dehumidifier, which has the advantages of improving dehumidification efficiency, saving energy and protecting the environment, extending the service life of the dehumidifier, further improving the applicability of the dehumidifier and optimizing the performance of the dehumidifier. DETAILED DESCRIPTION

[0053] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.

[0054] The present invention will be further described below in conjunction with specific embodiments: A dehumidification membrane comprises a membrane layer, a protective layer, and a support layer located between the membrane layer and the protective layer, wherein the protective layer is modified polyester, and the support layer is modified polyvinylidene fluoride. Calculated by mass, the membrane layer comprises 10-30 parts of inorganic salt, 5-20 parts of filler, and 50-80 parts of polymer.

[0055] The inorganic salt includes one of calcium chloride and lithium chloride. The filler includes one or more of carboxyl mesoporous silica, silver-zinc zeolite, and modified attapulgite. The polymer includes one or more of lauroyl sulfate deacetylated chitosan, polyether block polyamide, and polyvinyl alcohol. The polyether block polyamide uses Evonik Degussa EX9200, the carboxyl mesoporous silica uses Zhongke Keyou's carboxyl mesoporous silica, and the polyvinyl alcohol uses Japan Kuraray 60-98 polyvinyl alcohol.

[0056] The support layer is made of polyvinylidene fluoride and cellulose acetate.

[0057] The polyvinylidene fluoride comprises the following steps: Q1. Dissolve polyvinylidene fluoride and cellulose acetate in a mixed solvent of 70wt% N,N-dimethylacetamide and 30wt% acetone to obtain a first composite spinning solution; take polyvinylidene fluoride and cellulose acetate raw materials in a weight ratio of 1:1, and prepare a mixed solvent in a mass ratio of 1:1. The mass concentration of the composite spinning solution of polyvinylidene fluoride and cellulose acetate is about 24%, and the absolute viscosity is 5.5pa.s. The polyvinylidene fluoride uses Solvay 6008 polyvinylidene fluoride, and the cellulose acetate uses Eastman CA-398-3 cellulose acetate.

[0058] Q2. Dissolve polyvinylidene fluoride in a mixed solvent of N,N-dimethylacetamide and acetone to obtain a polyvinylidene fluoride spinning solution; the polyvinylidene fluoride spinning solution has a mass concentration of 10% and an absolute viscosity of 1.2 Pa.s.

[0059] Q3. Use two sets of electrospinning heads to extrude and electrospin using the first composite spinning solution and the polyvinylidene fluoride spinning solution respectively to form a three-layer composite structure non-woven fabric with different fiber diameters; the first layer and the third layer use the first composite spinning solution, and the middle layer uses the polyvinylidene fluoride spinning solution.

[0060] Q4. Introduce into a drying furnace at 120°C to remove residual solvent in the fiber.

[0061] The method for preparing the film layer comprises the following steps: T1. Add the polymer to N,N-dimethylacetamide solvent and stir at 80° C. for 2 hours using a magnetic stirrer until the polymer is completely dissolved to prepare a polymer solution; T2, dissolving an inorganic salt in a mixed solvent of 50-70wt% N,N-dimethylacetamide solution and 30-50wt% acetone solution, wherein the N,N-dimethylacetamide solution and the acetone solution are prepared in a mass ratio of 1:1, adding a filler and continuously stirring with a stirrer to obtain a mixed solution; T3. Gradually add the polymer solution into the mixed solution and stir until all components are completely dissolved to form a spinning solution; the spinning solution concentration is 10%.

[0062] T4, the spinning solution is placed in a vacuum dryer and vacuum degassed for 2 hours; T5. Inject the spinning solution into the spinning equipment, spin the spinning solution into fibers through electrospinning, and form a membrane layer on the receiving device.

[0063] The protective layer is made of polyester and polyvinyl alcohol.

[0064] The method for preparing the protective layer comprises the following steps: V1. Add polyester and polyvinyl alcohol to N,N-dimethylacetamide in a mass ratio of 80:20, and stir with a magnetic stirrer at 80° C. for 4 hours to obtain a polyester mixed solution; the polyester is Bayer 9385AU polyester, and the polyvinyl alcohol is Japanese Kuraray 60-98 polyvinyl alcohol.

[0065] V2. Pour the polyester mixed solution onto a flat plate, scrape it flat with a scraper to form a uniform film, and dry it at 80°C for 4 hours until the solvent is completely evaporated to obtain modified polyester.

[0066] The preparation method of the modified attapulgite comprises the following steps: M1. Grind and crush the attapulgite, sieve it to 80-200 mesh, add hydrochloric acid and stir it, the concentration of hydrochloric acid is 6 mol / L, mix it according to the solid-liquid ratio of 1:10, stir it for 2 hours, wash it with deionized water, centrifuge it and dry it at 100°C for 4 hours; M2. The acidified attapulgite was added to ethanol and fully dispersed by ultrasonic treatment for 30 minutes. The concentration of the obtained attapulgite-ethanol suspension was 5wt%. M3. Add the ethanol suspension of attapulgite into the silane coupling agent γ-methacryloxypropyltrimethoxysilane-ethanol working solution with a mass fraction of 2%, heat to 60°C, continue stirring for 4 hours, and after the reaction is completed, centrifuge, wash with ethanol, and dry to obtain modified attapulgite for later use.

[0067] The preparation method of lauroyl sulfate deacetylated chitosan comprises the following steps: N1, 5 g of the pretreated chitosan was mixed with 40 wt % sodium hydroxide solution, and reacted at a high temperature of 80° C. for 4 hours to obtain deacetylated chitosan; N2, weigh 5 grams of deacetylated chitosan to prepare a 10wt% deacetylated chitosan-ethanol solution, slowly drop 1.5 milliliters of lauroyl chloride under stirring, react at 40°C for 1 hour, wash with ethanol solvent after the reaction is completed and vacuum dry at 80°C overnight to obtain lauroyl chitosan; N3. Weigh 5 g of lauroyl chitosan to prepare a 10 wt% lauroyl chitosan-ethanol solution. Adjust the pH to 9, slowly drop 2 ml of dimethyl sulfate under stirring, and react at room temperature for 2 hours. After the reaction, pour the reaction solution into a large amount of deionized water to precipitate the product. Wash and dry to obtain lauroyl sulfate deacetylated chitosan for later use.

[0068] The preparation method of the silver-zinc-loaded zeolite comprises the following steps: P1. Grind the zeolite through a 60-80 mesh sieve, activate it with a 1-3 mol / L hydrochloric acid solution at room temperature, stir it for 1 hour at a solid-liquid ratio of 1:10, and after activation, wash the zeolite with deionized water until the washing liquid is neutral to remove excess hydrochloric acid and impurities, and dry it at 100° C. for 4 hours to obtain the pretreated zeolite; P2. Dissolve zinc nitrate in deionized water, add the pretreated zeolite to a 0.5 mM zinc nitrate mixed solution, and stir at 60-80° C. for 2-4 hours to obtain zinc-modified zeolite; P3, mixing a 0.5 mM silver nitrate solution with a 5 wt% glucose concentration, immersing the zinc-modified zeolite in the solution containing silver ions and glucose, and reacting at 60° C. for 2 hours; P4. After the reaction is completed, the silver-zinc zeolite is washed with deionized water, and the washed silver-zinc zeolite is vacuum dried at 80° C. overnight to obtain the silver-zinc zeolite for standby use.

[0069] A method for preparing a dehumidification membrane comprises the following steps: S1. Prepare a protective layer and a supporting layer respectively, and form a composite film layer by a compacting composite process; the thickness of the protective layer is 50 μm, and the thickness of the supporting layer is 150 μm.

[0070] S2. Prepare the membrane layer into a membrane spinning liquid, and coat the membrane spinning liquid on one side of the support layer of the composite membrane layer through an electrospinning process. The spinning liquid flow rate of the spinning process is 7 mL / h. A high-voltage DC power supply is used, the nozzle voltage is set at 30 kV, the receiving distance is 18 cm, the temperature is 25°C, the humidity is 35%, and the membrane layer thickness is 30 μm to obtain a dehumidification membrane.

[0071] Example 1 The preparation method of the dehumidification membrane is as follows: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0072] Calculated by weight, the film layer includes 20 parts of inorganic salt, 15 parts of filler and 65 parts of polymer.

[0073] The inorganic salt is calcium chloride. The filler includes carboxyl mesoporous silica and modified attapulgite. The polymer is polyether block polyamide and polyvinyl alcohol.

[0074] Example 2 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0075] Calculated by weight, the film layer includes 10 parts of inorganic salt, 5 parts of filler and 50 parts of polymer.

[0076] The inorganic salt is one of calcium chloride. The filler includes carboxyl mesoporous silica and silver-zinc zeolite. The polymer includes lauroyl sulfate deacetylated chitosan and polyvinyl alcohol.

[0077] Example 3 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0078] Calculated by weight, the film layer includes 30 parts of inorganic salt, 20 parts of filler and 80 parts of polymer.

[0079] The inorganic salt is calcium chloride. The filler includes silver-zinc zeolite and modified attapulgite. The polymer includes polyether block polyamide and polyvinyl alcohol.

[0080] Example 4 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0081] Calculated by weight, the film layer includes 15 parts of inorganic salt, 10 parts of filler and 70 parts of polymer.

[0082] The inorganic salt is lithium chloride. The filler includes carboxyl mesoporous silica, silver-zinc-loaded zeolite, and modified attapulgite. The polymer includes lauroyl sulfate deacetylated chitosan and polyether block polyamide.

[0083] Example 5 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0084] Calculated by weight, the film layer includes 18 parts of inorganic salt, 12 parts of filler and 60 parts of polymer.

[0085] The inorganic salt is one of lithium chloride. The filler includes carboxyl mesoporous silica, silver-zinc zeolite, and modified attapulgite. The polymer includes lauroyl sulfate deacetylated chitosan, polyether block polyamide, and polyvinyl alcohol.

[0086] Example 6 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0087] The support layer is modified polyvinylidene fluoride. Calculated by weight, the membrane layer comprises 15 parts of inorganic salt, 10 parts of filler and 60 parts of polymer.

[0088] The inorganic salt includes lithium chloride, the filler includes modified attapulgite, and the polymer includes lauroyl sulfate deacetylated chitosan.

[0089] Example 7 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0090] Calculated by weight, the film layer includes 10 parts of inorganic salt, 20 parts of filler and 70 parts of polymer.

[0091] The inorganic salt includes calcium chloride, the filler includes carboxyl mesoporous silica, silver-zinc-loaded zeolite, and modified attapulgite, and the polymer includes lauroyl sulfate deacetylated chitosan, polyether block polyamide, and polyvinyl alcohol.

[0092] Example 8 A method for preparing a dehumidification membrane comprises the following steps: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

[0093] A dehumidification membrane comprises a membrane layer, a protective layer, and a support layer located between the membrane layer and the protective layer, wherein the protective layer is modified polyester, and the support layer is modified polyvinylidene fluoride. Calculated by mass, the membrane layer comprises 25 parts of inorganic salt, 15 parts of filler, and 55 parts of polymer.

[0094] The inorganic salt includes lithium chloride, the filler is silver-zinc zeolite, and the polymer is polyether block polyamide.

[0095] Comparative Example 1 Compared with Example 1, Comparative Example 1 has the following differences: the filler is replaced with silicon dioxide, and the other components and steps of Comparative Example 1 are consistent with those of Example 1.

[0096] Comparative Example 2 Compared with Example 1, Comparative Example 2 has the following differences: the polymer is replaced with polyvinyl alcohol of Japan Kuraray 60-98, and the other components and steps of Comparative Example 2 are consistent with those of Example 1.

[0097] Comparative Example 3 Compared with Example 2, Comparative Example 3 has the following differences: the filler is replaced with silicon dioxide, and the other components and steps of Comparative Example 3 are consistent with those of Example 2.

[0098] Comparative Example 4 Comparative Example 4 has the following differences compared with Example 2: the polymer is replaced with polyvinyl alcohol of Japan Kuraray 60-98, and the other components and steps of Comparative Example 4 are consistent with those of Example 2.

[0099] Comparative Example 5 Compared with Example 5, Comparative Example 5 has the following differences: the support layer uses Solvay 6008 polyvinylidene fluoride, and the other components and steps of Comparative Example 4 are consistent with Example 2.

[0100] Comparative Example 6 Compared with Example 5, Comparative Example 6 has the following differences: the protective layer uses Bayer 9385AU polyester, and the other components and steps of Comparative Example 6 are consistent with those of Example 5.

[0101] Comparative Example 7 Comparative Example 7 has the following differences compared to Example 5: the method for preparing a dehumidification membrane comprises the following steps: preparing a membrane layer into a membrane layer spinning solution, coating the membrane layer spinning solution on one side of a support layer through an electrostatic spinning process, and obtaining a dehumidification membrane. The other components and steps of Comparative Example 7 are consistent with those of Example 5.

[0102] Comparative Example 8 Comparative Example 8 has the following differences compared to Example 5: the method for preparing a dehumidification membrane comprises the following steps: preparing a membrane layer into a membrane layer spinning solution, coating the membrane layer spinning solution on one side of the protective layer through an electrostatic spinning process, and obtaining a dehumidification membrane. The other components and steps of Comparative Example 8 are consistent with those of Example 5.

[0103] Table 1. Performance test results of Examples 1-8

[0104] Among them, the tensile strength and elongation at break are tested by a universal testing machine according to ASTM D882; the wet tensile strength is tested according to GB / T 465.2; the moisture permeability is tested according to GB / T 12704.1-2009, and the sample test area is 30cm 2 ; The antibacterial rate is tested using GB / T 20944.2-2007.

[0105] It can be seen from the performance test results of Examples 1-8 in Table 1 that, in the test items, the support layer and the protective layer can improve the overall tensile strength, elongation at break and wet tensile strength, the porosity of the membrane cloth is high, so that the moisture permeability has a corresponding effect, and the antibacterial properties of the filler or polymer can effectively improve the antibacterial properties of the dehumidification membrane.

[0106] The dehumidification membranes of Examples 1-8 significantly improve the porosity and pore connectivity, enhance the mechanical strength of the membrane, and improve the dehumidification efficiency by optimizing the composition and structure of the membrane layer, the support layer, and the protective layer.

[0107] The preparation methods of Examples 1-8 can ensure the excellent performance of the composite membrane layer, the high efficiency of the electrospinning membrane layer, the performance optimization of the dehumidification membrane, long-term stability, the controllability and flexibility of the preparation process, and the wide range of application fields. These beneficial effects make the prepared dehumidification membrane have a wide range of application prospects and market demand.

[0108] The dehumidification membranes of Examples 1-8 can be applied to dehumidifiers, and have the advantages of improving dehumidification efficiency, saving energy and protecting the environment, extending the service life of the dehumidifier, improving the applicability of the dehumidifier, and optimizing the performance of the dehumidifier.

[0109] Table 2. Performance test results of comparative examples 1-8

[0110] By comparing the performance test results of comparative examples 1-8 in Table 2 with the performance test results of embodiments 1-8 in Table 1, it can be seen that: Compared with Example 1, the carboxyl mesoporous silica and modified attapulgite in Example 1 have a larger specific surface area and mesoporous structure than the silica in Comparative Example 1. Its mesopores can provide a large number of adsorption sites, which helps to improve the pore structure of the film layer, increase the connectivity and regularity of the pores, so that water vapor can be transmitted more smoothly in the film layer, and the presence of carboxyl groups can enhance the adsorption of water molecules. The modified attapulgite has good adsorption and ion exchange capacity, and can form a channel in the film layer that is conducive to water vapor transmission, improve the connectivity of the pores inside the film layer, and improve the dehumidification performance of the dehumidification film. Therefore, the moisture permeability of Comparative Example 1 is inferior to that of Example 1.

[0111] Compared with Example 1, the polymer in Comparative Example 2 is replaced with polyvinyl alcohol. The polyether block polyamide in Example 1 has good flexibility, can maintain good physical properties, and is not easy to break. The polyether block polyamide has a certain selective permeability to water vapor, which allows water vapor to pass preferentially, while having a certain barrier effect on other gases, thereby improving the dehumidification efficiency of the dehumidification membrane. The polyether block polyamide can improve the flexibility of the membrane layer, so that the membrane layer maintains good mechanical properties. Therefore, the tensile strength, elongation at break and wet tensile strength of Comparative Example 1 are inferior to those of Example 1.

[0112] Comparative Example 3 is compared with Example 2, and Comparative Example 3 replaces the filler with silicon dioxide. Carboxyl mesoporous silica has a large specific surface area and mesoporous structure. Its mesopores can provide a large number of adsorption sites, which are helpful to improve the pore structure of the film layer, increase the connectivity and regularity of the pores, so that water vapor can be transmitted more smoothly in the film layer, and the presence of carboxyl groups can enhance the adsorption of water molecules. Silver-zinc-loaded zeolite also has antibacterial properties, which can inhibit the growth of mold on the film layer and improve the hygienic properties of the dehumidification membrane. Zeolite can play a role in enhancing structural stability in the film layer, which helps to improve the strength of the entire dehumidification membrane. Therefore, the antibacterial effect, moisture permeability, tensile strength, elongation at break and wet tensile strength of Comparative Example 3 are slightly worse than those of Example 2.

[0113] Comparative Example 4 is compared with Example 2. In Comparative Example 4, the polymer is replaced with polyvinyl alcohol. Lauroyl sulfate deacetylated chitosan has a certain adsorption effect on water vapor. Lauroyl sulfate deacetylated chitosan has antibacterial properties. At the same time, by introducing hydrophobic groups and sulfate groups, the mechanical strength and chemical resistance of the film layer are improved, and the functional groups on the molecular chain can interact with fillers or inorganic salts to enhance the integrity of the film layer. Lauroyl sulfate deacetylated chitosan helps to improve the film-forming properties of the film layer, so that the film layer can be uniformly formed on the support layer, ensuring the overall stability of the dehumidification film. Therefore, the antibacterial effect of Comparative Example 4 is slightly worse than that of Example 2.

[0114] Comparative Example 5 Compared with Example 5, Comparative Example 5 replaces the modified polyvinylidene fluoride of Example 5 with polyvinylidene fluoride. Example 5 uses two groups of electrospinning heads to extrude the first composite spinning solution and the polyvinylidene fluoride spinning solution respectively to form a non-woven fabric with a three-layer composite structure with different fiber diameters. This composite structure can combine the advantages of different fiber diameters. Finer fibers can provide a larger specific surface area, which is conducive to interaction with the external environment. For example, in a dehumidification membrane, it can increase the adsorption and diffusion area of ​​water vapor; while thicker fibers can provide better mechanical support and enhance the strength of the entire non-woven fabric. Therefore, the moisture permeability, tensile strength, elongation at break and wet tensile strength of Comparative Example 5 are worse than those of Example 5.

[0115] Compared with Example 5, Comparative Example 6 replaces the modified polyester in Example 5 with polyester. Example 6 modifies the polyester with hydrophilic polyvinyl alcohol, which can improve the moisture permeability of the polyester without affecting the mechanical properties. Therefore, the moisture permeability of Comparative Example 6 is worse than that of Example 5.

[0116] Compared with Example 5, in Comparative Example 7, the membrane spinning solution is directly coated on the support layer. Due to the lack of a protective layer, the tensile strength, elongation at break and wet tensile strength of Comparative Example 7 are inferior to those of Example 5.

[0117] Compared with Example 5, in Comparative Example 8, the membrane spinning solution is directly coated on the protective layer. Due to the lack of a support layer, the tensile strength, elongation at break and wet tensile strength of Comparative Example 8 are inferior to those of Example 5.

[0118] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A dehumidification membrane, characterized in that: The invention comprises a film layer, a protective layer and a support layer located between the film layer and the protective layer, wherein the protective layer is modified polyester and the support layer is modified polyvinylidene fluoride. Calculated by weight, the film layer comprises 10-30 parts of inorganic salt, 5-20 parts of filler and 50-80 parts of polymer.

2. A dehumidification membrane according to claim 1, characterized in that: The inorganic salt includes one of calcium chloride and lithium chloride.

3. A dehumidification membrane according to claim 1, characterized in that: The filler includes one or more of carboxyl mesoporous silica, silver-zinc-loaded zeolite, and modified attapulgite.

4. A dehumidification membrane according to claim 1, characterized in that: The polymer includes one or more of lauroyl sulfate deacetylated chitosan, polyether block polyamide, and polyvinyl alcohol.

5. The dehumidification membrane according to claim 1, characterized in that: The supporting layer is made of polyvinylidene fluoride and cellulose acetate, and the protective layer is made of polyester and polyvinyl alcohol.

6. A dehumidification membrane according to claim 1, characterized in that: The polyvinylidene fluoride comprises the following steps: Q1, dissolving polyvinylidene fluoride and cellulose acetate in a mixed solvent of N,N-dimethylacetamide and acetone to obtain a first composite spinning solution; Q2, dissolving polyvinylidene fluoride in a mixed solvent of N,N-dimethylacetamide and acetone to obtain a polyvinylidene fluoride spinning solution; Q3, using two sets of electrospinning heads, respectively using the first composite spinning solution and the polyvinylidene fluoride spinning solution for extrusion electrospinning to form a nonwoven fabric with a three-layer composite structure having different fiber diameters; Q4. Introduce into the drying furnace to remove the residual solvent in the fiber at 100-150°C.

7. The dehumidification membrane according to claim 1, characterized in that: The method for preparing the film layer comprises the following steps: T1. Add the polymer into the solvent and stir at 60-80°C for 2-4 hours using a magnetic stirrer until the polymer is completely dissolved to prepare a polymer solution; T2, dissolving the inorganic salt in the solvent, adding the filler and continuously stirring with a stirrer to obtain a mixed solution; T3, gradually adding the polymer solution into the mixed solution and stirring until all components are completely dissolved to form a spinning solution; T4, the spinning solution is placed in a vacuum dryer for vacuum degassing for 1-3 hours; T5. Inject the spinning solution into the spinning equipment, spin the spinning solution into fibers through electrospinning, and form a membrane layer on the receiving device.

8. The dehumidification membrane according to claim 1, characterized in that: The method for preparing the protective layer comprises the following steps: V1. Dissolving polyester and polyvinyl alcohol in a solvent, and stirring with a magnetic stirrer to obtain a polyester mixed solution; V2. Pour the polyester mixed solution onto a flat plate, scrape it flat with a scraper to form a uniform film, and dry it at 60-80°C for 2-4 hours until the solvent is completely evaporated to obtain modified polyester.

9. A method for preparing a dehumidification membrane, characterized in that: The following steps are involved: S1, preparing a protective layer and a supporting layer respectively, and forming a composite membrane layer by a compacting and laminating process between the protective layer and the supporting layer; S2. The membrane layer is prepared into a membrane layer spinning solution, and the membrane layer spinning solution is coated on one side of the support layer of the composite membrane layer through an electrostatic spinning process to obtain a dehumidification membrane.

10. An application of a dehumidification membrane, characterized in that: The invention comprises the use of the dehumidification membrane as described in any one of claims 1 to 8 in a dehumidifier.

Citation Information

Cited By

  • Low-change-rate slurry as well as preparation and application thereof

    CN119786121A